“Flow Void Sign”: Flow Artifact on T2-Weighted MRI Can Be an Indicator of Dural Defect Location in Ventral Type 1 Spinal CSF Leaks - Carlton Jones, Lalani; Edelmuth, Diogo G.L.; Butteriss, David; Scoffings, Daniel J. (American Journal of Neuroradiology, 2024)
Patients with spontaneous intracranial hypotension caused by type 1 dural defects typically have an epidural fluid collection on MRI. Still, the location of the defect is not usually readily identifiable on standard MRI sequences and can be at any point along the length of the collection. The most common location for type 1 leaks is ventral and, as such, these are most commonly associated with ventral predominant epidural fluid. Dynamic myelography (either digital subtraction myelography or dynamic CT myelography) is currently the standard of care for localizing the defect. We describe an imaging sign on T2-weighted images caused by CSF-flow egress at the site of the defect that may permit accurate prediction of the site of the CSF leak noninvasively. Importantly, this sign was only observed on 2D T2-weighted and STIR images and not on 3D acquisitions, which notably suppress artifacts. This has implications for optimal MRI spine protocol construction. This sign can be used to limit myelographic range, reduce radiation dose, and increase diagnostic confidence in dural defect location.dCTMdynamic CT myelographySIHspontaneous intracranial hypotension